Reproductive success in a female patient diagnosed with hypogonadotropic hypogonadism after in vitro fertilization: case report (Brazilian Journal of Health Research, 2025)
Introduction: Congenital hypogonadotropic hypogonadism (HHC) is a rare genetic condition, characterized by low levels of gonadotropins and sex steroids in the absence of anatomical and functional abnormalities of the hypothalamic-pituitary-gonadal axis, its incidence is approximately 1:10,000 – 1: 8,6000 and the male to female ratio is 3.6:1. Hormone replacement can be used in patients without reproductive desire, aiming at the emergence of secondary sexual characteristics, and in the presence of reproductive desire, the objective is ovulation and sperm production. Objective: Given its extremely low incidence, good evidence relevant to several aspects for reproductive medicine in HHC is weak. That said, this case report is intended to enrich the bibliography on the subject and add to the scientific community. Case report: Patient, 40 years old, nulligest, diagnosed with HHC sought medical care due to reproductive desire, the couple initially made attempts in 2018, without success, and carried out a new search for the procedure in 2021, when she underwent new ovarian stimulation, follicular aspiration and fertilization, obtaining five embryos, subjected to pre-implantation genetic analysis, selecting euploids for transfer. Two embryos were then transferred, with successful implantation and one of them evolving into a healthy newborn. Conclusion: In addition to the discrepant incidence between genders, making the diagnosis of HHC even rarer in females, the moment of diagnosis in these cases may occur later. Low-complexity reproductive techniques can be offered, but a significant proportion of these patients will need assisted reproduction techniques.
Keywords: Congenital hypogonadotropic hypogonadism; Assisted reproductive techniques; Fertility; Ovarian reserve